Sampling and analytical methods for the geochemical study of the sediment of reservoirs in the Dominican Republic: preliminary results - Araújo, Joana (2017)
This paper characterizes the geochemical profile of the sediments of two dam reservoirs from the Dominican Republic focusing on the sedimentary processes involved and on determining the main sources of the deposited material. Surface and deep sediments were sampled as well as rocks of the drainage basins in order to compare geochemical signatures of the parent rock and of the materials deposited at the bottom of the two dams. This study comprises a geochemical analysis of major, minor, trace and rare earth elements. A petrographic analysis of the different lithotypes was carried out. The preliminary geochemical analysis of sediments showed high Ca and Mg content levels, demonstrating the important influence of the carbonate rocks, present on the basin, to the sedimentation processes.